Dependences between the footwear fitting and feet structure in girls of third-grade primary school - EWA PUSZCZALOWSKA-LIZIS; PAULINA ZARZYCZNA; WIOLETTA MIKULAKOVA (Akademia Wychowania Fizycznego i Sportu w Gdansku, 2020)
Background: The study aimed to study dependences between the footwear fitting and feet structure in girls of third grade of primary school. Material and methods: The research tool was the podoscope CQ-ST. The footwear fitting to the feet of the examined children was tested using the Clevermess device. Results: Statistically significant relationships between the frequency of varus deformity of the Vth toe of the right foot and the width fitting of the outdoor footwear were found (p=0.027). Statistically significant relationships between the length of the indoor footwear and the heel angle (γ) of the left foot have also been noted (p = 0.038). Conclusions: Conclusions: Children with a wider forefoot wear longer shoes, which is why there is a need to take into account differences in the foot width in the production of footwear used indoors. The use of too short footwear, without free space that is necessary for the proper setting of the foot during movement or load, is a factor leading to excessive lateral arching. Wearing too wide shoes affects the formation of varus deformity of the Vth toe of the right foot.